Knowledge Level and Treatment Adherence among Pulmonary Tuberculosis Patients: A Cross-Sectional Study - Agus, Al Ihksan; Rosmiati (Omni Nursing Journal, 2025)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and remains a major cause of morbidity and mortality, particularly in developing countries. TB transmission occurs through airborne droplets, and successful treatment requires strict long-term adherence to medication to prevent treatment failure and drug resistance. Patient knowledge is considered an important factor influencing adherence behavior. Objective: This study aimed to analyze the relationship between knowledge level and treatment adherence among tuberculosis (TB) patients. Methods: This quantitative observational study employed a cross-sectional design and involved 120 TB patients who were undergoing treatment at primary health care facilities. Data were collected using a structured questionnaire to assess patients’ knowledge of TB and its treatment, as well as a medication adherence measurement tool, such as the Morisky Medication Adherence Scale (MMAS). Data were analyzed using the Chi-square test with a significance level of p < 0.05. Results: The results showed a statistically significant relationship between knowledge level and treatment adherence among TB patients (p < 0.05), indicating that patients with higher knowledge levels were more likely to adhere to TB treatment. Conclusion: A higher level of knowledge is significantly associated with better treatment adherence among TB patients. Strengthening patient education should be prioritized as part of TB control programs to improve treatment outcomes.